Exploring the missionary church - Webb, Barry G.; Moore Theological College, Sydney, Aust. (Sydney, NSW ANZEA, 1993)
Includes bibliographical references
The Exploration series is based on papers presented at the Moore College annual Explorations seminar.
Keywords: Evangelicalism; Church -- mission